Implementation of Student Management in Improving the Potential of Public Elementary School Students - Ahmad Dandi; Indah Ardhini; Amaliyah Amaliyah; Salwa Az Zahra; Siti Hani Hardiyani Azizah (EDUJAVARE: International Journal of Educational Research, 2026)
Student Management is a process of mentoring students, in developing their abilities so that they can develop optimally. The focus is on managing activities in a planned, directed, and sustainable manner. A common problem in schools is the suboptimal management of student management in supporting the growth of students' academic and non-academic potential. This study aims to (1) evaluate how student management is implemented to improve student abilities, (2) and identify factors that help and hinder its implementation at SDN Rawa Buntu 01. This study uses a qualitative approach with a case study method. Data collection techniques include observation, interviews, and document examination from the principal, teachers, educational staff, and students. Data analysis is carried out in three stages: data reduction, data presentation, and conclusions. The results of the study indicate that student management, which includes planning, organizing, implementing, and supervising, is able to strengthen students' potential in terms of academics, interests and talents, and social attitudes. Supporting factors are the existence of a structured coaching program, self-development services, and active participation from teachers and parents. Meanwhile, obstacles encountered include limited facilities and differences in student characteristics. This research provides theoretical benefits in strengthening understanding of educational management and practical benefits as a basis for schools to improve student management to maximize student potential.